A PLAYFUL PROPOSAL FOR TEACHING AND LEARNING ANALYTICAL CHEMISTRY (REMUNOM, 2025)
Mediated learning is a pedagogical approach in which a facilitator acts as a bridge between the studentand the content, helping to achieve a deeper and more meaningful understanding of the content. Among the various forms of mediation, playful activities stand out as an effective strategy to engage students and make learning more playful and dynamic. In this context, the presented work proposes the creation of a didactic game entitled "Precipitation Volumetry: The Chemical Challenge", developed to assist in teaching this subject in higher education courses. The game was designed using low-cost materials, making it easier to implement. It consists of a board, a set of cards with questions of different levels of difficulty, dice and player pawns. The proposal aims to make the assimilation of Analytical Chemistry concepts more interactive, reducing students' resistance to the subject and encouraging more active participation in the learning process.